A Short‐Step Synthesis of 1, 6‐Methano[10]annulene‐3, 4‐dicarboximides and Their Benzene‐, Naphthalene‐, and Thiophene‐Annulated Compounds (Eur. J. Org. Chem. 27/2014). Issue 27 (September 2014) - Oda, Mitsunori; Nakamura, Tomomi; Neha, Miyako; Miyawaki, Daisuke; Ohta, Akira; Kuroda, Shigeyasu; Miyatake, Ryuta
Abstract : The cover picture shows a rapid stream in a valley of the Hirayu area in the Gifu Prefecture located in the middle of the Japanese mainland. The schemes show an improved one‐pot reaction with phosphorane reagents, along the stream, and the previously reported multistep reactions from dicarbaldehydes to 1, 6‐methano[10]annulene‐dicarboximides. The one‐pot procedure was successfully applied to the synthesis of the arene‐annulated 1, 6‐methano[10]annulenes. Details are discussed in the article by M. Oda et al. on p.5976 ff . Even after the eminent achievements by the late Dr. E. Vogel, the field of 1, 6‐methano[10]annulene chemistry is still interesting and fertile. The authors thank Mr. Yoshimitsu Kumai in our laboratory for his great help in preparing this cover picture.